Troubleshooting Analysis of the Gandroom Cooling System on the KM. Lambelu - Rifqi Taufiqul Hakim; Antonius Edy Kristiyono; Shofa Dai Robbi; Monika Retno Gunarti; Novitasari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The ship's refrigeration system is crucial for the preservation of crew food during the voyage, but a failure on KM. Lambelu resulted in temperatures of only -5°C (fish) and -6°C (meat) versus the target of -18°C. This study aims to analyze troubleshooting using mixed methods convergent parallel with FMEA for RPN, repair impact, and post-replacement evaluation of the compressor. The population is KM. Lambelu's engineering officers, a purposive sample of 30 respondents. Instruments are Likert questionnaires (S, O, D), logbooks, photographs; validity/reliability test analysis, RPN = S × O × D, qualitative reduction. The results show the highest RPN 50 compressor, replacement restores pull-down from 25°C to -23°C. Conclusion: replacement effectively restores optimal function, prioritize preventive inspections.